Pengaruh Kecepatan Dan Keandalan Pelayanan Terhadap Kepuasan Konsumen Yang Dimediasi Oleh Kinerja Karyawan Dalam Menggunakan Jasa Keagenan Pada PT Bukit Prima Bahari - Akbar, Achmad; Wadud, Muhammad (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The research was conducted in Palembang at PT. Bukit Prima Bahari, Palembang Branch Office located at Jalan Stasiun Kertapati, Palembang City. PT. Bukit Prima Bahari is engaged in maritime transportation services and ship agency. The purpose of this research is to determine the influence of service speed and service reliability, mediated by employee performance, on customer satisfaction. The respondents selected for this study were 126 individuals from 14 companies. The types of data used were primary and secondary data. The primary data for the research were collected through the distribution of questionnaires to respondents, aiming to gather information about services based on aspects of speed, reliability, and employee performance. The research results indicate that service speed and service reliability have a positive and significant impact on customer satisfaction. Additionally, the research found that employee performance, as a mediating variable, has a significant influence. In this study, it was revealed that without the support of skilled employees, they cannot work quickly and reliably, thereby failing to provide satisfaction to customers. Based on these research findings, it is implied that there will be implications for the company's operations to enhance their services to customers, thus having a positive long-term impact on PT. Bukit Prima Bahari.